Pengaruh Strategi Pemasaran Dalam Upaya Meningkatkan Pendapatan Petani Dalam Perspektif Ekonomi Islam (Studi Pada Petani Jagung di Desa Soriutu Kecamatan Manggelewa Kabupaten Dompu NTB) - Ningsih, Sonia Yulia; Wahono, Budi; Ramadhan, Tri Sugiarti (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This research is to find out how corn farmers' marketing strategies increase income, as well as knowing the Islamic economics review of marketing strategies. This research is descriptive qualitative, namely research that is explanatory and aims to obtain a complete picture of something being researched. The data collection techniques used were observation, interviews and documentation.The results of the research show that the marketing strategy implemented by corn farmers in Soriutu Village, Manggelewa District, Dompu Regency, NTB, is to increase income, by implementing a product marketing mix system, price, place, promotion. The products marketed have quality from superior seeds using quality fertilizer. Pricing is in accordance with product quality. The promotion implemented is still very simple, namely using personal selling or direct promotion (personal selling). The marketing mix method is stated to be quite good. According to the Islamic economic perspective, it can be concluded that the marketing strategy implemented is in accordance with Islamic principles, the products offered are halal, pricing does not harm both parties, the business location is very strategic and easy to reach for consumers, promotions are carried out honestly, correctly, gently and with sincerity to serve. consumer. Keyword: Strategy, Marketing, Revenue, and Islamic economic perspective